KONSEP KEADILAN DALAM PERSPEKTIF EKONOMI ISLAM - Permana, Yoga; Nisa, Fauzatul Laily (Jurnal Ekonomi Syariah Darussalam, 2024)
Justice is a condition in which ideal moral truth is achieved, both in the context of objects and individuals. Justice becomes a very crucial principle especially in an effort to overcome the economic and social injustices that often arise in the conventional economic system. Islamic economics as a distinct field of study, emerged as a response to the perceived shortcomings of the conventional economic system. The purpose of this study is to analyze the concept of justice in the perspective of Islamic economics. This research uses the literature study method to examine the concept of justice in the perspective of Islamic economics. This method involves collecting and analyzing data from various relevant literature sources such as books, journal articles, and other publications that discuss justice and Islamic economics. The concept of justice in Islamic economics creates balance and equality in various economic transactions. The concept of justice in the perspective of Islamic economics is a crucial element that must be upheld to build trust and harmony in every economic activity, as well as to ensure that every individual can contribute to collective welfare without pursuing personal interests alone